Toy Academy - Some assembly required - Lynch, Brian (Scholastic Press, 2018)
Attending Toy Academy to train in the art of play, misfit little toy Grumbolt, who is not an action figure, a stuffed animal or a collectible, resolves to find his proper place before a rival plot by Evil Toy Academy compels Grumbolt to take a dangerous risk to save his school
Sequel: Ready for action
Keywords: Toys / Juvenile fiction; Schools / Juvenile fiction; Play / Juvenile fiction; Illustrated children's books; Schools / Fiction; Play / Fiction; JUVENILE FICTION / Action & Adventure; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Toys, Dolls & Puppets; Play; Schools; Toys; Toys / Fiction; School stories; Children's stories; Fiction; Juvenile works; Kinderbuch